ANALISIS VALIDITAS BAHAN AJAR STRUKTUR ALJABAR BERBASIS STRATEGI ABDUKTIF-DEDUKTIF - Suryani Lukman, Hamidah; Mulyanti, Yanti (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2017)
This paper explains about the analysis of validity of abstract algebra teaching materials based on abductive-deductive strategy which is the first stage on research and development study, expert judgement. The instrument used in this research is validation sheet consisting of five aspects of the assessment, namely the feasibility of the material aspect, the feasibility of the language aspect, the feasibility of the presentation aspect, the feasibility of teaching effect on the student learning process, and the feasibility of the overall display aspect. Validator involved in this research is four experts in mathematics education. The data of this research are analyzed descriptively. The result of this research shows that 80% of eligibility criteria of the material aspect have been fulfilled are categorized as very good (4.21), 90% of language aspect eligibility criteria have been fulfilled and categorized excellent (4.81), 85% of the presentation aspect eligibility criteria have been fulfilled and categorized as very good (4.50), 80% of the criteria for the effect of teaching materials on the students' learning process have been fulfilled as very good category (4.25), and 80% of eligibility criteria of the overall display aspect have been fulfilled and categorized as very good (4.25). Based on these data, 85% of the criteria for the assessment of the feasibility of Abstract algebra teaching materials based on the abductive-deductive strategy have been fulfilled, categorized as very good (4.35), and suitable for use in learning.